Convergent Validity of the Central Sensitization Inventory in Chronic Whiplash-Associated Disorders; Associations with Quantitative Sensory Testing, Pain Intensity, Fatigue, and Psychosocial Factors. Issue 12 (16th September 2020) - Hendriks, Erwin; Voogt, Lennard; Lenoir, Dorine; Coppieters, Iris; Ickmans, Kelly
Abstract: Objective: Central sensitization is present in different pain conditions, including chronic whiplash-associated disorders. In the absence of a gold standard method of assessment to determine the presence of central sensitization, quantitative sensory testing is currently understood as an optimal proxy. Laboratory sensory testing is, however, not feasible in clinical practice, and the Central Sensitization Inventory was developed as an alternative. The aim of the current study was to evaluate the convergent validity of the Central Sensitization Inventory in chronic whiplash-associated patients by determining the association between the Central Sensitization Inventory and quantitative sensory testing, pain intensity, fatigue, and psychosocial factors. Methods: A total of 125 chronic whiplash-associated patients completed multiple questionnaires and were subjected to pressure pain thresholds and temporal summation. Results: . The Central Sensitization Inventory showed a strong association with constructs of general psychopathology, anxiety, distress, depression, and somatization in chronic whiplash-associated disorders. Moderate correlations were found with fatigue and intrusive and avoidant phenomena after a variety of traumatic events. No significant association was found between the Central Sensitization Inventory and pressure pain thresholds and temporal summation, nor between the Central Sensitization Inventory and other pain measurements. Conclusions: Overall, we found that the Central Sensitization Inventory is better in identifying the psychosocial factors related to central sensitization in chronic whiplash-associated disorders than the central nervous system adaptations. Thus, the convergent validity of the Central Sensitization Inventory appears to be only partially present in chronic whiplash-associated disorders.